2022
DOI: 10.1371/journal.pone.0272133
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Covid 19 during the third wave of infection in Norwegian patients with type 1 diabetes

Abstract: Objective To study the fear of Covid 19 infection among Norwegian patients with type 1 diabetes. Research design and methods Fear of Covid 19 scale, a validated scale assessing the fear of Covid 19, was sent electronically to 16255 patients with type 1 diabetes in May 2021. The items are rated on a scale from 1 to 5 (total scores from 7 to 35). The higher the score, the greater the fear. Results 10145 patients, 52% of the Norwegian adult type 1 diabetes population, completed the questionnaire. The mean tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(30 reference statements)
0
1
0
1
Order By: Relevance
“…Nevertheless, there is a dearth of studies that have examined the general population after the second wave, particularly in Europe, with a predominant focus on healthcare professionals or patients with chronic diseases. For instance, a study conducted by Ueland GÅ et al in mid-2021 revealed that patients with type 1 diabetes exhibited lower levels of fear towards COVID-19 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is a dearth of studies that have examined the general population after the second wave, particularly in Europe, with a predominant focus on healthcare professionals or patients with chronic diseases. For instance, a study conducted by Ueland GÅ et al in mid-2021 revealed that patients with type 1 diabetes exhibited lower levels of fear towards COVID-19 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studien sendte ut et validert spørreskjema under pågående pandemi i mai 2021 (The fear of covid-19 scale) der pasientene ble bedt om å gradere sin angst for covid 19, sett i lys av at de har en kronisk sykdom og er kategorisert som risikopasienter. Studien ble publisert i Plos One i juli 2022 (2). Videre ble det sendt ut en mer omfattende registrering av hvordan pasientene har vaert rammet av pandemien, også via Helse-Norge, i desember 2021.…”
unclassified